The Astonishing Behavior of Electric Eels - Catania, Kenneth C. (Frontiers in Integrative Neuroscience, 2019)
The remarkable physiology of the electric eel (Electrophorus electricus) made it one of the first model species in science. It was pivotal for understanding animal electricity in the 1700’s, was investigated by Humboldt and Faraday in the 1800’s, was leveraged to isolate the acetylcholine receptor in the 20th century, and has inspired the design of new power sources and provided insights to electric organ evolution in the 21st century. And yet few studies have investigated the electric eel’s behavior. This review focuses on a series of recently discovered behaviors that evolved alongside the eel’s extreme physiology. Eels use their high-voltage electric discharge to remotely control prey by transcutaneously activating motor neurons. Hunting eels use this behavior in two different ways. When prey have been detected, eels use high-voltage to cause immobility by inducing sustained, involuntary muscle contractions. On the other hand, when prey are hidden, eels often use brief pulses to induce prey twitch, which causes a water movement detected by the eel’s mechanoreceptors. Once grasped in the eel’s jaws, difficult prey are often subdued by sandwiching them between the two poles (head and tail) of the eel’s powerful electric organ. The resulting concentration of the high-voltage discharge, delivered at high-rates, causes involuntary fatigue in prey muscles. This novel strategy for inactivating muscles is functionally analogous to poisoning the neuromuscular junction with venom. For self-defense, electric eels leap from the water to directly electrify threats, efficiently activating nociceptors to deter their target. The latter behavior supports a legendary account by Alexander von Humboldt who described a battle between electric eels and horses in 1800. Finally, electric eels use high-voltage not only as a weapon, but also to efficiently track fast moving prey with active electroreception. In conclusion, remarkable behaviors go hand in hand with remarkable physiology.